Hubungan Motivasi dengan Perilaku tentang Pemeriksaan Payudara Sendiri (Sadari) Pada Siswi Kelas VII dan VIII di SMPN 1 Cireunghas Wilayah Kerja Puskesmas Cireunghas Kabupaten Sukabumi - Mawla Khairunnisa Nur Iskandar; Susilawati Susilawati; Femy Melia Rahmawati (Universitas Malahayati Lampung, 2026)
ABSTRACT Breast cancer is one of the leading causes of death among women aged 15–49 years. One of the measures that can be taken is early detection through Breast Self-Examination (BSE). The behaviour regarding BSE is influenced by many factors, one of which is motivation. Analysing the relationship between motivation and behaviour regarding self-breast examination (SADARI) among Year 7 and Year 8 schoolgirls. This is a correlational study employing a cross-sectional approach. The population comprised all female students in Years 7 and 8 at SMPN 1 Cireunghas, totalling 194 respondents. The sample consisted of 131 respondents, selected using proportional random sampling. Data was collected using a questionnaire. The data was analysed using Somersd’s test. The results of the study indicate that the majority of respondents demonstrated high motivation and good behaviour. The results of the Somers’d test showed a p-value of 0.001, which indicates a significant association between motivation and behaviour regarding self-examination of the breasts (BSE). There is a relationship between motivation and behaviour regarding self-breast examination (BSEI) among Year 7 and Year 8 female students at SMPN 1 Cireunghas within the Cireunghas Public Health Centre catchment area, Sukabumi Regency. Keywords: Breast Cancer, Motivation, Behaviour, Adolescents, BSE ABSTRAK Kanker payudara merupakan salah satu penyebab kematian utama pada wanita usia 15–49 tahun. Salah satu upaya yang dapat dilakukan adalah melalui deteksi dini berupa Pemeriksaan Payudara Sendiri (SADARI). Perilaku dalam melakukan SADARI banyak dipengaruhi oleh faktor, salah satunya adalah motivasi. Menganalisis hubungan motivasi dengan perilaku tentang pemeriksaan payudara sendiri (SADARI) pada siswi kelas VII dan VIII. Jenis penelitian korelasional dengan pendekatan cross-sectional. Populasi melibatkan seluruh siswi kelas VII dan VIII di SMPN 1 Cireunghas sebanyak 194 responden. Sampel berjumlah 131 responden menggunakan proportional random sampling. Pengumpulan data menggunakan kuesioner. Analisis data menggunakan uji somers’d. Hasil studi menunjukan bahwa sebagian besar responden memiliki motivasi tinggi dan perilaku yang baik. Hasil uji somers’d menunjukan nilai p-value 0,001 yang berarti ada hubungan motivasi dengan perilaku tentang pemeriksaan payudara sendiri (SADARI). Terdapat hubungan motivasi dengan perilaku tentang pemeriksaan payudara sendiri (SADARI) pada siswi kelas VII dan VIII di SMPN 1 Cireunghas Wilayah Kerja Puskesmas Cireunghas Kabupaten Sukabumi. Kata Kunci: Kanker Payudara, Motivasi, Perilaku, Remaja, SADARI.